Quality of life of persons affected by leprosy in an endemic district, West Bengal, India - Pitchaimani Govindharaj; Sampathkumar Srinivasan; Joydeepa Darlong (Wolters Kluwer Medknow Publications, 2018)
Introduction: Leprosy still remains a public health problem in India. Stigma and associated psychosocial problems are common in leprosy and may affect the quality of life (QoL). This study aimed to assess the QoL of the person affected by leprosy living in Purulia district, West Bengal. Methods: A cross-sectional study was conducted among 358 persons affected by leprosy above the age of 18 years and who were reporting at tertiary leprosy referral hospital, Purulia, West Bengal, from April to July 2017. The World Health Organization QoL (WHOQOL-BREF) scale was used to measure the QoL and the scale had four domain; physical health, psychological health, social relationship, and environmental health. Results: Of the 358 respondents, 41% were female, 60% were aged between 18 and 45 years, and 58% were literate. Half of the participants (55%) were farmer and labor, and 75% of the participants' family income was below Rs. 5000 per month. One hundred and forty-four (40%) participants had physical disability. There was a highly significant difference seen among the person affected by leprosy between those with visible deformity and no deformity in four domains. The participants with visible deformity had lower QoL than the person without deformity. Conclusion: The study observed that the person affected by leprosy with visible deformity had lower QoL. Early detection and management would prevent the deformity and might improve the QoL of persons affected by leprosy.